Preparation method of low-carbon alcohol adsorbent

By treating alkaline solution, vulcanizing and calculating on ZSM-5 molecular sieve, its pore structure and lipophilicity are adjusted, which significantly improves the adsorption capacity of low-carbon alcohol adsorbents, and solves the problem of insufficient adsorption amount of existing ZSM-5 molecular sieve. , achieving efficient low-carbon alcohol adsorption effect.

CN119114010AActive Publication Date: 2024-12-13SHANDONG QILU HUAXIN HIGH TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411223656.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The existing ZSM-5 molecular sieve has a low adsorption of low-carbon alcohols, which affects the purity of the material and industrial production efficiency.

Method used

The high-silicon ZSM-5 molecular sieve was treated with alkaline solution, and then vulcanized and calcined, the silicon-aluminum ratio and pore structure were adjusted, the adsorption capacity was enhanced, and the lipophilicity and stability of the molecular sieve were improved through binder molding.

Benefits of technology

The adsorption amount of low-carbon alcohol adsorbents was significantly improved, with the adsorption amount of ethanol exceeding 19.8%, and the performance was improved by nearly 50%, solving the problem of poor adsorption of ZSM-5 type molecular sieve, and the material economy was good.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a low-carbon alcohol adsorbent, and belongs to the technical field of adsorbents. The preparation method comprises the following steps: (1) preparing an alkaline solution, wherein the mass ratio of inorganic base to acid salt to water in the solution is 1: (0.1-10): (10-300); (2) mixing a high-silicon ZSM-5 molecular sieve with the alkaline solution prepared in the step (1) according to a solid-to-liquid ratio of 1: (1-15), and stirring at 25-95 DEG C for 0.5-5 hours; filtering and washing with water to obtain a product 1; (3) adding the product 1 into a vulcanizing solution, stirring and reacting at 25-115 DEG C for 0.5-5 hours, washing with water, and filtering to obtain a product 2; (4) adding a binder, an acidic solution and water into the product 2, and carrying out extrusion molding to obtain a product 3; and (5) roasting the product 3 at 500-1000 DEG C for 0.5-5 hours to obtain the low-carbon alcohol adsorbent. According to the invention, the pore volume and the pore diameter are increased, so that the low-carbon alcohol adsorption capacity is improved; through vulcanization, the hydrophobic capacity of the molecular sieve is enhanced, and the lipophilicity of the molecular sieve is improved; the problem that the ZSM-5 type molecular sieve is poor in adsorption is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a low-carbon alcohol adsorbent, and belongs to the technical field of adsorbents. Background Art

[0002] In current industrial production, molecular sieves are widely used. When purifying materials, molecular sieves can effectively adsorb mixed ethanol molecules and then strip them off to ensure the purity of industrial materials and facilitate production operations. However, the existing molecular sieve structures for adsorbing ethanol molecules are mostly directly prepared using single silicon source and aluminum source materials, which not only affects the uniformity of material mixing, but also has a poor adsorption effect. Summary of the invention

[0003] According to the background problem, the problem to be solved by the present invention is:

[0004] The existing ZSM-5 molecular sieve has a low adsorption capacity for low-carbon alcohols.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A preparation method of a low-carbon alcohol adsorbent, the preparation method comprising:

[0007] A method for preparing a low-carbon alcohol adsorbent comprises the following steps:

[0008] (1) preparing an alkaline solution, wherein the mass ratio of each component in the solution is inorganic base: acid salt: water = 1: 0.1-10: 10-300;

[0009] (2) taking a high-silicon ZSM-5 molecular sieve and the alkaline solution prepared in step 1 in a solid-liquid mass ratio of 1:1 to 15, stirring at 25 to 95° C. for 0.5 to 5 h; then filtering and washing with water to obtain product 1;

[0010] (3) adding product 1 to the sulfide solution, stirring and reacting at 25-115° C. for 0.5-5 h, washing with water, and filtering to obtain product 2;

[0011] (4) adding a binder, an acidic liquid and water to the product 2, and extruding the product 2 to obtain a product 3;

[0012] (5) The product 3 is calcined at 500-1000°C for 0.5-5h to obtain a low-carbon alcohol adsorbent.

[0013] Preferably, the inorganic base in step 1 is one or both of sodium hydroxide solution and potassium hydroxide solution; the acid salt is one or more of sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate.

[0014] Preferably, the mass ratio of the inorganic base to the acid salt in the alkaline solution is 1:1-10.

[0015] Preferably, in step 2, the stirring temperature is 55 to 85° C., and the stirring time is 1 to 2 hours.

[0016] Preferably, the solute in the sulfiding liquid in step 3 is one or more of sulfosalicylic acid, sodium sulfosalicylate, toluenesulfonic acid and o-toluenesulfonic acid, and the mass concentration of the sulfiding liquid is 0.1-10%.

[0017] Preferably, in step 3, the solid-liquid mass ratio of the product 1 to the sulfide liquid is 1:1-100.

[0018] Preferably, in step 3, the stirring temperature is 75° C. to 100° C., and the stirring time is 1 to 2 h.

[0019] Preferably, it is characterized in that in step 4, the mass ratio of product 2: binder: acidic liquid: water is 1: 0.1-0.5: 0.01-0.5: 0.5-10.

[0020] Preferably, in step 4, the binder is one or both of sesbania powder and cellulose; and the acidic liquid is one or more of acidic silica sol, oxalic acid and phosphoric acid.

[0021] The method of the present invention comprises first treating a high-silicon ZSM-5 molecular sieve with an alkaline solution system, then sulfiding the treated sample, and then filtering, washing, molding, and roasting to obtain a low-carbon alcohol adsorbent. The method uses an alkaline solution system during the treatment, and can obtain molecular sieves with different silicon-aluminum ratios, different mesopore sizes, specific surface areas, and pore volumes by adjusting the ratio of inorganic bases to acid salts, and obtain adsorption conditions with high specific surface areas and rich mesopores without destroying the molecular sieve skeleton structure; the subsequent sulfidation treatment can reduce the oxygen content on the molecular sieve surface and reduce the molecular sieve skeleton polarity, thereby improving the lipophilicity of the molecular sieve; under high-temperature roasting, the sulfur element can be more stably combined with the molecular sieve, and -OH can be reduced, thereby enhancing the adsorption capacity of low-carbon alcohols on the molecular sieve surface.

[0022] The beneficial effects of the present invention are:

[0023] The low-carbon alcohol adsorbent prepared after treatment according to the method of the present invention has the following characteristics: the ZSM-5 molecular sieve treated with an alkaline solution has mesoporous properties, increases the pore volume and pore diameter, thereby improving the adsorption capacity of low-carbon alcohols, and after sulfurization, not only the hydrophobicity of the molecular sieve itself is enhanced but also the lipophilicity of the molecular sieve is improved. Calcination under high temperature conditions can not only make the sulfur element more stably combined with the molecular sieve, but also reduce -OH, thereby enhancing the adsorption capacity of low-carbon alcohols on the surface of the molecular sieve, and specifically improve the adsorption capacity of low-carbon alcohols in VOC gases in applications. The adsorption capacity of low-carbon alcohols in ZSM-5 molecular sieves is 10% to 15%, while the ethanol adsorption capacity of the low-carbon alcohol adsorbent prepared by the present invention exceeds 19.8%, and some experiments can exceed 23%, the performance is improved by nearly 50%, and the problem of poor adsorption of ZSM-5 molecular sieves is solved.

[0024] The low-carbon alcohol adsorbent prepared by this technology not only has a high low-carbon alcohol adsorption capacity, but also has cheap and easily available raw materials for preparation, and has good economic efficiency. DETAILED DESCRIPTION

[0025] Example 1

[0026] 58g of sodium hydroxide solution, 1000g of deionized water, and 70.0g of sodium carbonate were added to a 2000mL beaker, heated to 60°C in a water bath, and then 150.0g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 300 without a template was added, and the mixture was treated in a water bath for 2h, and then the mixture was rapidly cooled to room temperature and filtered, and washed to neutrality to obtain product 1. 400g of water was added to a 1000mL beaker, and 5g of sulfosalicylic acid was added and stirred, and the mixture was heated to 100°C in a water bath, and then 50g of product 1 was added, and the temperature was kept constant for 1.0h, and the mixture was rapidly cooled, filtered, washed to neutrality, and dried in an oven at 120°C for 12h, and then crushed to obtain product 2. To 20 g of product 2, add 2 g of sesbania powder, 0.2 g of acidic silica sol, and 10 g of water, stir evenly, and extrude using a 1.6 mm circular orifice plate to obtain product 3, which is placed in an oven and dried at 120 ° C for 8 h, and calcined in a muffle furnace at 600 ° C for 1 h. The obtained sample is a low-carbon alcohol adsorbent.

[0027] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), the water absorption rate of the low-carbon alcohol adsorbent was measured to be 8.1%, and according to the molecular sieve static ethanol adsorption determination method, the ethanol adsorption rate of the ethanol adsorbent was measured to be 23.5%; the ethanol adsorption capacity of the ZSM-5 molecular sieve is between 10% and 15%, while the ethanol adsorption capacity of the low-carbon alcohol adsorbent prepared by the present invention exceeds 23%.

[0028] Example 2

[0029] 100g of sodium hydroxide, 1000g of deionized water, 2g of potassium carbonate and 8g of sodium carbonate were added to a 2000mL beaker, heated to 25°C in a water bath, and then 200.0g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 300 without a template was added, and the mixture was treated in a water bath for 5h, and then the mixture was quickly cooled to room temperature and filtered, and washed to neutrality to obtain product 1. 500g of water was added to a 1000mL beaker, 3g of sodium sulfosalicylate was added and stirred, and the mixture was heated to 25°C in a water bath, and then 50g of product 1 was added, and the temperature was kept constant for 5h, and the temperature was quickly cooled, filtered, washed to neutrality, placed in an oven at 120°C for 12h, and then crushed to obtain product 2. Add 2g of sesbania powder, 30g of acidic silica sol, and 200g of water to 20g of product 2, stir well, and extrude using a 1.6mm circular orifice plate to obtain product 3. Place product 3 in an oven, dry at 120°C for 8h, and calcine at 500°C in a muffle furnace for 5h. The obtained sample is a low-carbon alcohol adsorbent.

[0030] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), the water absorption rate of the low-carbon alcohol adsorbent was measured to be 7.2%. According to the molecular sieve static ethanol adsorption determination method, the ethanol adsorption rate of the ethanol adsorbent was measured to be 19.8%.

[0031] Example 3

[0032] 3g of sodium hydroxide, 900g of deionized water, and 30.0g of sodium carbonate were added to a 2000mL beaker, heated to 95°C in a water bath, and then 150.0g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 300 without a template was added, and the mixture was treated in a water bath for 0.5h, and then the mixture was rapidly cooled to room temperature and filtered, and washed to neutrality to obtain product 1. 450g of water was added to a 1000mL beaker, and 15g of sulfosalicylic acid, 5g of sodium sulfosalicylate, 15g of toluenesulfonic acid, and 15g of o-toluenesulfonic acid were added and stirred, and the mixture was heated to 115°C in a water bath, and then 100g of product 1 was added, and the temperature was kept constant for 0.5h, and the mixture was rapidly cooled, filtered, washed to neutrality, and dried in an oven at 120°C for 12h, and then crushed. Add 10g of sesbania powder, 5g of oxalic acid and 5g of phosphoric acid, and 100g of water to 20g of product 2, stir well, and extrude using a 1.6mm circular orifice plate to obtain product 3. Place product 3 in an oven, dry at 120°C for 8h, and calcine at 1000°C in a muffle furnace for 0.5h. The obtained sample is a low-carbon alcohol adsorbent.

[0033] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), the water absorption rate of the low-carbon alcohol adsorbent was measured to be 7.5%. According to the molecular sieve static ethanol adsorption determination method, the ethanol adsorption rate of the ethanol adsorbent was measured to be 22.5%.

[0034] Example 4

[0035] 15g of sodium hydroxide, 15g of potassium hydroxide, 990g of deionized water, and 30.0g of sodium bicarbonate were added to a 2000mL beaker, heated to 90°C in a water bath, and then 70.0g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 300 without a template was added, and the mixture was treated in a water bath for 1h, and then the mixture was rapidly cooled to room temperature and filtered, and washed to neutrality to obtain product 1. 499.5g of water was added to a 1000mL beaker, and 0.5g of sulfosalicylic acid was added and stirred, and the mixture was heated to 90°C in a water bath, and then 50g of product 1 was added, and the temperature was kept constant for 1h, and the temperature was rapidly cooled, filtered, washed to neutrality, and placed in an oven at 120°C for 12h and then crushed. Add 5g of cellulose and 5g of sesbania powder, 10g of acidic silica sol, and 100g of water to 20g of product 2, stir well, and extrude using a 1.6mm circular orifice plate to obtain product 3. Place product 3 in an oven, dry at 120°C for 8h, and calcine at 1000°C in a muffle furnace for 0.5h. The obtained sample is a low-carbon alcohol adsorbent.

[0036] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), the water absorption rate of the low-carbon alcohol adsorbent was measured to be 6.2%. According to the molecular sieve static ethanol adsorption determination method, the ethanol adsorption rate of the ethanol adsorbent was measured to be 25.6%.

[0037] Example 5

[0038] 10g potassium hydroxide, 480g deionized water, and 10.0g potassium bicarbonate were added to a 2000mL beaker, heated to 90°C in a water bath, and then 500.0g ZSM-5 molecular sieve with a silicon-aluminum ratio of 300 without a template was added, and the mixture was treated in a water bath for 1h, and then the mixture was rapidly cooled to room temperature and filtered, and washed to neutrality to obtain product 1. 490g water was added to a 1000mL beaker, and 10g sulfosalicylic acid was added and stirred, and the mixture was heated to 90°C in a water bath, and then 5g product 1 was added, and the temperature was kept constant for 1h, and the temperature was rapidly cooled, and the mixture was filtered and washed to neutrality, and then placed in an oven at 120°C for 12h and then crushed. Add 2g of sesbania powder, 5g of acidic silica sol and 3g of phosphoric acid, and 100g of water to 20g of product 2, stir well and extrude using a 1.6mm circular orifice plate to obtain product 3. Place product 3 in an oven, dry at 120°C for 8h, and calcine at 800°C in a muffle furnace for 0.5h. The obtained sample is a low-carbon alcohol adsorbent.

[0039] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), the water absorption rate of the low-carbon alcohol adsorbent was measured to be 8.1%. According to the molecular sieve static ethanol adsorption determination method, the ethanol adsorption rate of the ethanol adsorbent was measured to be 23.5%.

[0040] The ethanol adsorption capacity of the low-carbon alcohol adsorbent prepared by the present invention exceeds 19.8%, and most experiments can exceed 23%, which is nearly 50% higher than the performance of commercially available products, and solves the problem of poor adsorption of ZSM-5 molecular sieves.

Claims

1. A method for preparing a low-carbon alcohol adsorbent, It is characterized in that The following steps are involved: (1) preparing an alkaline solution, wherein the mass ratio of each component in the solution is inorganic base: acid salt: water = 1: 0.1-10: 10-300; (2) taking a high-silicon ZSM-5 molecular sieve and the alkaline solution prepared in step 1 in a solid-liquid mass ratio of 1:1 to 15, stirring at 25 to 95° C. for 0.5 to 5 h; then filtering and washing with water to obtain product 1; (3) adding product 1 to the sulfide solution, stirring and reacting at 25-115° C. for 0.5-5 h, washing with water, and filtering to obtain product 2; (4) adding a binder, an acidic liquid and water to the product 2, and extruding the product 2 to obtain a product 3; (5) The product 3 is calcined at 500-1000°C for 0.5-5h to obtain a low-carbon alcohol adsorbent.

2. A method for preparing a low-carbon alcohol adsorbent according to claim 1, It is characterized in that The inorganic base in step 1 is one or both of sodium hydroxide solution and potassium hydroxide solution; the acid salt is one or more of sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate.

3. The method for preparing a low-carbon alcohol adsorbent according to claim 1, It is characterized in that The mass ratio of the inorganic base to the acid salt in the alkaline solution is 1:1-10.

4. The method for preparing a low-carbon alcohol adsorbent according to claim 1, It is characterized in that In step 2, the stirring temperature is 55-85° C. and the stirring time is 1-2 h.

5. The method for preparing a low-carbon alcohol adsorbent according to claim 1, It is characterized in that In step 3, the solute in the sulfiding liquid is one or more of sulfosalicylic acid, sodium sulfosalicylate, toluenesulfonic acid and o-toluenesulfonic acid, and the mass concentration of the sulfiding liquid is 0.1-10%.

6. The method for preparing a low-carbon alcohol adsorbent according to claim 1, It is characterized in that In the step 3, the solid-liquid mass ratio of the product 1 to the sulfide liquid is 1:1-100.

7. The method for preparing a low-carbon alcohol adsorbent according to claim 1, It is characterized in that In step 3, the stirring temperature is 75° C. to 100° C., and the stirring time is 1 to 2 hours.

8. The method for preparing a low-carbon alcohol adsorbent according to claim 1, It is characterized in that In the step 4, the mass ratio of product 2: binder: acidic liquid: water is 1: 0.1-0.5: 0.01-0.5: 0.5-10.

9. The method for preparing a low-carbon alcohol adsorbent according to claim 1, It is characterized in that In step 4, the binder is one or both of sesbania powder and cellulose; the acidic liquid is one or more of acidic silica sol, oxalic acid and phosphoric acid.

Citation Information

Patent Citations

  • ZSM-5 modification treatment method

    CN104628011A

  • Preparation method of mesoporous ZSM-5 molecular sieve

    CN115784252A

  • Sulfur removal process

    US6048451A

  • KR20230149352A